Asterococcus superbus as a biosorbent of copper, zinc, cadmium and lead: adsorption isotherm and kinetic modelling - Areco, María del Mar (2014)
The adsorption capacity of copper, zinc, cadmium and lead by Asterococcus superbus, a freshwater microalgae, was studied in batch mode. The Langmuir, Freundlich, Temkin and Dubinin?Radushkevich models were applied and results demonstrate that for all cases the Langmuir model best describes the adsorption process and that A. superbus isotherm followed the bisorption series, Zn > Cu > Pb > Cd. Kinetic studies demonstrate that the adsorption of zinc and copper follows a pseudo-second-order kinetic model, and that of cadmium and lead follows a pseudo first-order kinetic model. Natural waters present an increasing concentration of heavy metals, mainly due to the effluent discharge in these type or reservoires. The importance of the present work is to contribute to the study of new methods to diminish the presence of heavy metals in natural waters.